Double Insurance for OC: miRNA-Mediated Platinum Resistance and Immune Escape - Zou, Xueqin; Zhao, Yangjing; Liang, Xiuting; Wang, Hui; Zhu, Yanling; Shao, Qixiang (Frontiers in Immunology, 2021)
Ovarian cancer is the leading cause of death among all gynaecological malignancies and platinum remains the first-line chemotherapy for ovarian cancer patients, despite the recent progress in cancer therapy. The emergence of drugs resistance, especially platinum-based chemotherapy, results to disease progression, recurrence and poor prognosis in ovarian cancer patients. MicroRNAs (miRNAs) are small noncoding RNAs, regulating gene expression at the transcriptional level and accumulating evidence, have indicated their crucial roles in platinum resistance. Generally, the mechanisms responsible for miRNAs in platinum resistance include reduced intracellular accumulation, aberrant DNA repair, apoptosis pathway inactivation, and other key signaling pathways. Consequently, considerable effort has been devoted to develop potential strategies targeting miRNAs to improve platinum sensitivity and clinical outcome for ovarian cancer patients. In this review, we summarize miRNAs involved in platinum resistance and discuss their possible mechanisms and signaling pathways for therapeutic strategies in ovarian cancer. Further understanding of miRNAs roles in platinum resistance is essential to combat chemoresistance and may open new avenues for improving ovarian cancer therapy.